The decision-making process of synthetic pesticide use in agricultural communities in Colombia: a grounded theory approach - Ysabel Polanco López de Mesa (Revista Facultad Nacional de Salud Pública, 2020)
Objectives: to explore the decision-making process of agricultural workers associated with pesticide use and exposure; to deduce whether these processes differ between pesticide users and non-users; and to analyze the characteristics of these differences. Methodology: This study used a grounded theory approach to understand the decision-making process for pesticide use/non-use among agricultural workers in San Cristobal, Colombia. This study involved participant observation, individual interviews, and focus groups. Results: the theory developed to explain the decision-making process for pesticide use showed several categories including: the prospect of having a good harvest, efficient pest control, habituation to the use of pesticides, feeling obligated to use them, poor knowledge about pesticides, believing that pesticides increase the quality of the products, positive attitudes towards pesticide use, family support towards pesticide use, community pressure and acceptance, economic fear, and market pressure. In the non-pesticide user group categories included: having better health, pesticides considered harmful for human health, pesticides being deleterious for the environment, habituation to working without pesticides, family and economic support, and negative attitude towards pesticide use. The decision-making process for personal protective equipment (PPE) use encompassed categories such as: feelings of powerlessness, economic difficulties, and belief that equipment is not necessary. Discussion: The decision-making process for pesticide use in agricultural communities is complex and varies between pesticide users and non-users. Conclusions: It is important to consider the intricate process of pesticide use in order to orient interventions in the agricultural sector.